NEW INFORMATION TECHNOLOGY AND ITS CAPACITIES FOR MODELING OF GEOSYSTEMS - Vladimir I. Gunin (Геодинамика и тектонофизика, 2015)
Numerical solution of the Navier-Stokes equations for free and forced convection in solid and porous media is challenging as an evolution equation for pressure is lacking. An information technology is proposed on the basis of a new system of hydrodynamic equations. It provides for distinguishing between free and forced convection components and allows estimation of parameters of the cumulative convective flow by calculating values of its two components. A classical system of equations of the ellipticparabolic type is developed for solving the problems of heat and mass transfer. The system describes vortex structures which occur in the gravitational field in all media in case of density stratification. A majority of the available computation methods and schemes can be applied for numerical solutions of the proposed system; therefore modeling can be simplified, while the scope of the system’s application can be expanded. Possible applications of the proposed information technology are demonstrated by examples showing how problems of low-mantle plume and diapir formation and rifting in the lithosphere-crust system can be solved.